ضوابط عمل النيابة العامة في التشريع الجزائري - حليتيم محمد رضا - طيب باي عبد الباسط (المسيلة, 2023)
تهدف هذه قواعد الى محاولة تسليط الضوء على مهام النيابة العامة و ضوابطها باعتبارها ممثلة المجتمع ، و قد تناولنا فيها بالدراسة مفهوم النيابة العامة و طبيعتها القانونية و الخصائص التي تتميز بهم ، و كذا تشكيلتها و اختصاصاتها، كما وضحنا طريقة عمل النيابة العامة من خالل تحريكها للدعوى العمومية في مختلف مراحلها ، كما تطرقنا الى القيود التي تغل عمل النيابة العامة في تحريك الدعوى العمومية و المتمثلة في الشكوى ، الطلب و اإلذن . Abstract : These rules aim to try to shed light on the functions of the Public Prosecution and its controls as a representative of society, and we have dealt with the study of the concept of the Public Prosecution and its legal nature and characteristics that characterize them, as well as its composition and competencies, as we explained the method of work of the Public Prosecution through its movement of the public prosecution in its various stages, as we touched on the restrictions that overwhelm the work of the Public Prosecution in moving the public lawsuit, represented in the complaint, request and permission.
Keywords: ضوابط العمل - النيابة العامة - التشريع الجزائري